Politicising dark tourism sites: evidence from Cyprus - Farmaki, Anna; Antoniou, Katerina (My University, 2017)
Purpose: This paper aims to extend understanding on how the tourist experience at dark heritage sites is directed and consequently influences the narratives of cultural heritage. By discussing the way dark heritage sites are projected by suppliers, the paper anticipates to advance knowledge on the nexus between dark tourism and heritage and to offer insights into the management of dissonant heritage sites. Design/methodology/approach: The cases of two opposing national museums in the divided island of Cyprus are presented and discussed in an attempt to illustrate how dissonant heritage interpretation in a post-conflict context is often the product of political direction, commemorating the past and to a great extent influencing the future of a society. Findings: National struggle museums represent dark heritage sites, which evoke emotions pertinent to ethnic identity reinforcement. Evidently, the management of such sites is in opposition to peace-building efforts taking place in a post-conflict context. The paper concludes that visitation to dark heritage sites is culturally driven rather than death-related and suggests that efforts consolidate to target specific segments of visitors, if the reconciliation potential of dark tourism is to be unleashed. Originality/value: Insofar, minimal attention has been paid on the conditions of the supply of dark heritage sites and the role of suppliers in influencing culture-based issues including collective memory and national identity. This paper addresses this gap in literature and advances understanding on the developmental elements defining dark heritage tourism, by identifying and discussing trajectories between dark tourism and politics.
Keywords: Cyprus; Dark tourism; Heritage; Museums